Leitura e escola: um estudo sobre a visão de professores e alunos sobre a prática de leitura - Baiarde, Elaine Cristina (2008)
This research has as subject the study of the reading and its education in the classroom. To argue this, it is presented conception of reading, the act to read and to understand. In the other hand, if describes the strategies of reading understanding that are used at the moment of the processing of the text. The theoretical referencial of the National Curricular Parameters if makes appear, with intention to explain the education of reading in classroom. Also if it presents the influence of the literal sorts in education and objective reading.The development of the activity of this work is: to present the theoretical beddings on the reading education and to describe as a group of professors and pupils understand reading and its education in the classroom. The research is organized in three chapters. The first one presents the conception of reading, the act to read and to understand. On the second has as referencial theoretician of teach and learn reading and the quarrels of PCN (Parâmetros Curriculares Nacionais). In this chapter also if it explains the influence of the literal sorts in the reading education. The third chapter presents the quarrels on reading and education of a group of professors and pupils of a school of the particular net. The data presented and argued in this chapter happen of questionnaire considered to the teachers of the inquired pertaining to school unit; of activity carried through in classroom with pupils of Basic and finally, of questionaire and activity considered to pupils of college. Explained, in this study, that the education of reading practised in the school selected for analysis contributes so that the pupil if becomes a critical and reflective reader in the society contemporary, therefore for what if it perceives in this school, education and, consequently the practical reader makes with that the pupils assume themselves of the characteristics of the diverse texts that is studied in the lessons it understands and them of coherent form, thus accomplishing the full participation of these pupils in the world scholar